FARMER’S INTENTION ON CLIMATE CHANGE ADAPTATION - Dwi Renita; Ratya Anindita (Agricultural Socio-Economics Journal, 2017)
The purposes of this research is to describe local knowledge of farmer’s perception toward climate change and to analyze farmer’s intention toward climate change adaptation based on the theory of planned behavior. The sampling method used is simple random sampling with the population is the farmers in the research location. Data was analyzed using descriptive statistics analysis and also structural equation modeling – partial least square (SEM-PLS) for generating information regarding farners behavior toward climate change. The results showed that 57.5 percent of respondents said that the intensity of rainy season and the temperature were changing significantly and 40 percent respodents also agree that the temperature was getting higher. There was 65% of respondents said that the climate change was driven by deforestration or logging. However, there was 17.5% of respondents said that factories have caused the climate change. Impact of climate change cause increasing pests and diseases attacking paddy crops and decreasing significantly of land productivity. For the structural equation modeling, subjective norm and perceived behavior control infuence positively the intention of farmers’ adaptation toward climate change.